2009
DOI: 10.1124/jpet.109.161265
|View full text |Cite
|
Sign up to set email alerts
|

Cardamonin Is a Bifunctional Vasodilator that Inhibits Cav1.2 Current and Stimulates KCa1.1 Current in Rat Tail Artery Myocytes

Abstract: An in-depth analysis of the effects of cardamonin, 2Ј,4Ј-dihydroxy-6Ј-methoxychalcone, on rat tail artery preparations was performed by means of whole-cell patch-clamp recordings of Ca v 1.2 Ca 2ϩ [I Ca(L) ] or Ba 2ϩ [I Ba(L) ] current as well as K Ca 1.1 currents in single myocytes and by measuring contractile responses in endothelium-denuded isolated rings. At a holding potential (V h ) of Ϫ80 mV, cardamonin decreased both I Ba(L) and I Ca(L) in a concentration-dependent manner with similar pIC 50 values. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Cardamonin was shown to block vascular L‐type Ca 2+ (Ca v 1.2) channels while stimulating K Ca 1.1 channels, thus behaving as a bifunctional vasodilatory agent (Fusi et al . ).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Cardamonin was shown to block vascular L‐type Ca 2+ (Ca v 1.2) channels while stimulating K Ca 1.1 channels, thus behaving as a bifunctional vasodilatory agent (Fusi et al . ).…”
mentioning
confidence: 97%
“…For example, two Citrus flavonoids, namely (AE)-naringenin and naringin, were shown to stimulate large conductance Ca 2+ -activated K + (K Ca 1.1) channels, thus accounting for their vasodilatory action (Saponara et al 2006). Cardamonin was shown to block vascular L-type Ca 2+ (Ca v 1.2) channels while stimulating K Ca 1.1 channels, thus behaving as a bifunctional vasodilatory agent (Fusi et al 2010).…”
mentioning
confidence: 99%
“…Only recently, Matsui et al reported that apple procyanidins relax rat aortic rings possibly by activation of several potassium channels [48]. Vasodilation via synergistic effects of potassium current activation and calcium current reduction has been suggested for amentoflavone, kolaviron, pinocembrin, luteolin, and cardamonin [49][50][51][52][53]. Effects of flavonoids on vascular electrophysiology have been summarized in Table 1.…”
Section: Effects Of Flavonoids On Other Vascular Potassium Channelsmentioning
confidence: 99%
“…) is a chalcone that was first isolated from the seeds of Amomum subulatum (Bheemasankara Rao et al , ), and subsequently from other Zingiberaceae family plants (Tewtrakul et al , ; Ahmad et al , ; Liu et al , ). The bioactivity of cardamonin has been studied in many of the plant substrates from where it had been previously isolated, for example: cardamonin isolated from Alpinia katsumadai was found to cause vasorelaxation in mice artery rings preconstricted by various antagonists (Wang et al , ); cardamonin from fruits of Alpinia rafflesiana showed anti‐inflammatory properties in cellular models (Ahmad et al , ); cardamonin from Boesenbergia pandurata demonstrated antimutagenic effect upon activation of heterocyclic amines (Trakoontivakorn et al , ), in vitro inhibitory activity against the HIV‐1 protease (Tewtrakul et al , ) and bifunctional vasodilator properties (Fusi et al , ) among other very promising health promoting properties (Cho et al , ; Liao et al , ; Yadav et al , ).…”
Section: Introductionmentioning
confidence: 99%